Festivals of Opet, the Valley, and the New Year : their socio-religious functions - Fukaya, Masashi, 1977- (Archaeopress Egyptology, 2020)
This volume compares the religious and social functions of the Ancient Egyptian festivals of Opet, the Valley, and the New Year. Until now, detailed study of the New Year Festival has only been carried out with reference to the Greco-Roman period; this study turns its attention to the New Kingdom.